Pengaruh Pemberian Ekstrak Rumput Kebar (Biophytum Petersianum Klotzsch) Terhadap Fertilitas Tikus Jantan (Rattus Novergicus L) - Azlina Azlina (Departement of Mathematics Education, 2023)
Rumput kebar was one a clump plantation that was known as medicinal plant. It only can be found in Kebar sub-district, Manokwari, Irian Jaya. The reduction of spermatozoa fertility due to the poisonous material such as Borax (Na2B4O710H2O). Borax is the one of chemical substance can inhibit spermiosis and then followed by testicles atrophy. The research aimed to try out induction of rumput kebar extract in order to increase spermatozoa quality of male rats which was impacted by borax. The samples contained of 48 male rats (Rattus norvegicus L) which were 2 months old and 150-200g in weight. There were two treatments. The first was using of rumput kebar extract in male rats which were reduced in reproduction activity. The second one was using of rumput kebar extract in normal rats. Rumput kebar extract was given orally to male rat every day (0.0945 mg/g of body weight in dose) by duration of 7 days, 14 days, 21 days, and 28 days. The result showed that the rumput kebar extract increased testicle weight in infertile rat beginning on 7th day. Rumput kebar extract increased spermatozoa concentration from 7th to 21st day (P0.05). In other hand, rumput kebar extract decreased abnormality morphology of spermatozoa significantly on 28th day (P<0.05) while it didn’t affect spermatozoa concentration significantly on 28 th day (P>0.05). In other hand, rumput kebar extract decreased abnormality morphology of spermatozoa significantly on 28th day (P<0.05). Viability of spermatozoa increased significantly on 21st day and 28th day (P<0.05). Rumput kebar could only incresed morphology performance of spermatozoa up to 50% in normal rats. It could also incresed male rat’s body weight.